Answer:
D. -4x(x - 2)(x+3)
Explanation:
We are given the following trinomial:
![-4x^3 - 4x^2 + 24x](https://img.qammunity.org/2022/formulas/mathematics/college/27nd60p95c3lcbfe4w5mbfmjn5na32evs9.png)
-4x is the common term, so:
![-4x((-4x^3)/(-4x) - (4x^2)/(-4x^3) + (24x)/(-4x)) = -4x(x^2+x-6)](https://img.qammunity.org/2022/formulas/mathematics/college/no29mv785hb1tv4uf4ark7w5gh9xkaezzy.png)
The second degree polynomial can also be factored, finding it's roots.
Solving a quadratic equation:
Given a second order polynomial expressed by the following equation:
.
This polynomial has roots
such that
, given by the following formulas:
x² + x - 6
Quadratic equation with
![a = 1, b = 1, c = -6](https://img.qammunity.org/2022/formulas/mathematics/college/6e1k0vztpcb8n766g950tt36n2bu6c5h58.png)
So
![\Delta = 1^(2) - 4(1)(-6) = 25](https://img.qammunity.org/2022/formulas/mathematics/college/o2bd8xr4rmqcroppkz7pe1tnlgi9x75hgv.png)
![x_(2) = (-1 - √(25))/(2) = -3](https://img.qammunity.org/2022/formulas/mathematics/college/7zbri1dmk4onmpyysq2g93hebj82x4i4et.png)
So
![x^2 + x - 6 = (x - 2)(x - (-3)) = (x - 2)(x + 3)](https://img.qammunity.org/2022/formulas/mathematics/college/5bu222ue7punpwf81wkkfaos3xnep8fhnl.png)
The complete factorization is:
![-4x(x^2+x-6) = -4x(x - 2)(x + 3)](https://img.qammunity.org/2022/formulas/mathematics/college/tm0tpid6fcqmgvibju9tk2jnjt75lhj5in.png)
Thus the correct answer is given by option d.